Virtual reality technology in electronic cigarette prevention and cessation intervention: A systematic review - Picholas Kian Ann Phoa·; Mexmollen Marcus; Ching, Sin Siau; Yin, How Wong; Charles Sharma Naidu; Chrisminder Dain; Lei, Hum Wee (Springer Nature, 2025)
Purpose of Review The rising prevalence of electronic cigarettes (e-cigarettes) use, especially among adolescents and young adults, underscores the need for novel and innovative strategies to promote cessation. Various reviews have demonstrated the effectiveness of VR in treating substance use disorders. In smoking interventions, VR is utilized to deliver cue exposure therapy, acceptance-avoidance tasks, behavioral training, and skill development. However, it remains uncertain whether these approaches can be effectively adapted for e-cigarette cessation. This review aims to examine the characteristics, effectiveness, and implementation of virtual reality (VR) interventions for e-cigarettes prevention and cessation. Recent Findings Upon searching four databases between 2003 until December 2023, this review included four documents detailing two game-based VR interventions for e-cigarette prevention among adolescents. The studies demonstrated promising outcomes in improving adolescents’ knowledge and perceptions on e-cigarettes and in maintaining low intention to experiment with e-cigarette use. Users feedback indicated a generally positive user experience with the VR interventions. Summary While these VR interventions have been well-received and show promise in supporting abstinence among non-users, the existing evidence is insufficient to draw definitive conclusions, highlighting key research gaps. Notably, existing interventions focus mainly on prevention among adolescents in high-income countries, lack standardized implementation outcome measures, and seldom incorporate physiological verification for cessation. Addressing these gaps is essential for optimizing VR interventions and ensuring their effectiveness across diverse populations and settings.